Documythtary a feminist critical frame analysis on how myth and reality coalesce in Philippine documentary cinema - Rendon, Aiza R.; Arumpac, Adjani G. (Quezon City University of the Philippines, Diliman, 2025)
This research introduces the documythtary, a form of documentary where myth and reality converge within Philippine documentary cinema. It explores how this fusion challenges conventional notions of documentary as a medium rooted in factual representation. Using Aswang, Alunsina, and Tungkung Langit as case studies, produced during and before the Duterte administration, the study examines the intersections of myth, history, and social struggle in cinematic narratives. Drawing from a reflexive feminist standpoint, it employs Critical Frame Analysis to investigate how myth functions not only as narrative but as a framing device that shapes sociopolitical meaning. The research builds on Alice Guillermo’s Social Realism framework and proposes an update that reflects evolving cultural and aesthetic forms. Central to this inquiry is the argument that the documythtary serves both as a conceptual lens and an interpretive method for understanding present realities with a deeper historical consciousness. Findings suggest that the documythtary expands the expressive and political possibilities of documentary cinema, positioning it as a creative, critical, and reflexive medium. This study contributes to contemporary discussions in media theory by redefining how “reality” is constructed and perceived in documentary film.
Thesis
Keywords: Motion pictures -- Philippines -- History and criticism; Feminism -- Documentary films -- Philippines